PENGARUH KESEIMBANGAN KEHIDUPAN KERJA TERHADAP KINERJA GURU WANITA DI MADRASAH ALIYAH SWASTA KABUPATEN BOGOR: Keseimbangan Kehidupan Kerja; Kinerja Guru; Guru Wanita; Madrasah - Rahmawati, Ima; Rifatunisa, Adinda; Apriani, Risa; Rustini, Titin (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2025)
This study aims to analyze the influence of work-life balance on the performance of female teachers at private Madrasah Aliyah in Bogor Regency. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (SEM-PLS). A total of 127 female teachers were selected through purposive sampling. The research instrument was a Likert-scale questionnaire measuring three indicators of work-life balance and four indicators of teacher performance. The outer model testing showed that all indicators were valid and reliable. The inner model test revealed that work-life balance significantly influenced teacher performance with a path coefficient of 0.615 and a t-statistic value of 8.423. These results indicate that better balance between personal life and work leads to higher performance among female teachers. The findings suggest that institutional support for women’s dual roles significantly contributes to improving teaching quality. Therefore, attention to work flexibility and psychological well-being is essential for developing human resources in Islamic educational institutions.